Analisis Debit Puncak untuk Perencanaan Sistem Drainase di Kawasan Teknopark Pelalawan - Indriatmoko, Robertus Haryoto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2019)
ABSTRACTA drainage system is an infrastructure that plays an important role for regions such as in Pelalawan technopark. Drainage system design needs to be carried out comprehensively to obtain the results of the predicted regional channel system analysis based on maximum daily rainfall data in the area. Thus, any rain falling in each sub-watershed within the region can be properly flowed, through the channel system in the four main drainages and does not cause flooding in the area. The methodology for the analysis of drainage systems is carried out through 4 comprehensive stages, starting with delineation of the four sub-watersheds in the area and performing sub-watershed morphometry until mapping process of the main drainage system of the Pelalawan technopark area. The results of peak discharge analysis is derived from the calculation of rain plan/predicted rain results in the 25-year return period, the Petarik sub-watershed has value of 158.21 m3/sec, while the Bedaguh Guntung watershed, Ã‚Â the Kahayan sub-watershed, and the Langgam watershed have results about 53.64 m3/dt, 30.56 m3/sec, and 34.16 m3/sec respectively. If the drainage system is to be built in the Technopark area, one main channel must be provided in each sub-watershed with channel capacity by the peak discharge. If the four main channels have been prepared, the Technopark Region will be free of flooding for the planning period from the rain with a 25 year return period.Keyword:Ã‚Â Technopark,Ã‚Â infiltration, rainfall, return periode, peak discharge, drainage capacityÃ‚Â ABSTRAKRancangan sistem Ã‚Â drainase adalah sebuah infrastruktur yang memegang peranan penting termasuk untuk kawasan seperti di teknopark Pelalawan. Perencanaan sistem drainase perlu dilaksanakan dengan baik untuk mendapatkan hasil analisis sistem saluran kawasan yang diprediksi berdasarkan data Ã‚Â hujan hujan harian maksimum dalam kawasan tersebut. Ã‚Â Dengan demikian, setiap hujan Ã‚Â yang jatuh di dalam setiap sub DAS dalam kawasan dapat dialirkan dengan baik, melalui sistem saluran pada keempat drainase utama dan tidak menimbulkan banjir dalam kawasan. Metodologi untuk analisis sistem Ã‚Â drainase, dilakukan melalui 4 tahap yaituÃ‚Â yang dimulai dengan melakukan deliniasi terhadap keempat sub DAS dalam kawasan dan melakukan morfometri sub DAS untuk mendapatkan data luas dari masing-masing sub DAS, kemiringan lereng, koefisien runoff, dan time of consentrationÃ‚Â (tc). hingga pemetaan sistem drainase utama Ã‚Â kawasan teknopark Pelalawan. Hasil analisis Ã‚Â debit puncak Ã‚Â pada 4 sub DAS Ã‚Â dalam kawasan teknopark yang berasal dari perhitungan hujan rencana/ hujan hasil prediksi pada periode ulang 25 tahun, untuk ke 4 adalah Sub DAS Petarik sebesar 158,21 m3/dt, sub DAS Bedaguh Guntung sebesar 53,64 Ã‚Â m3/dt. Sub DAS Kahayan sebesar Ã‚Â 30,56 m3/dt Ã‚Â dan Ã‚Â Sub DAS Langgam sebesar 34,16 m3/dt. Apabila dalam kawasan Teknopark tersebut akan dibangun sistem drainase, maka harus disediakan 1 (satu) buah saluran utama di setiap Ã‚Â Sub DAS dengan kapasitas saluran sesuai dengan besarnya sesuai dengan debit puncak. Jika keempat saluran utama tersebut telah disiapkan maka Kawasan Teknopark akan dapat terbebas dari banjir untuk periode perencanaan dari hujan dengan periode ulang 25 tahun.Kata kunci:Ã‚Â Teknopark, infiltrasi, hujan, periodeÃ‚Â ulang, debit puncak, kapasitas saluran